Immigration and House Prices in the UK. (6th September 2014) - Sá, Filipa
<x xml:space="preserve">Abstract</x> This article studies the effect of immigration on house prices in the UK. It finds that immigration has a negative effect on house prices and presents evidence that this negative effect is due to the mobility response of the native population. Natives respond to immigration by moving to different areas and those who leave are at the top of the wage distribution. This generates a negative income effect on housing demand and pushes down house prices. The negative effect of immigration on house prices is driven by local areas where immigrants have lower education.